Goethezeit & Romantik : Zeichnungen, Aquarelle und Gouachen von 1778 bis 1893. (Hamburg : Le Claire Kunst, 2010)
Graff, Anton ; Mechau, Jakob Wilhelm ; Dies, Albert Christoph ; Hackert, Jakob Philipp ; Gmelin, Wilhelm Friedrich ; Birmann, Peter ; Von Kobell, Wilhelm ; Kobell, Franz ; Radl, Anton ; Dinkel, Markus ; Riepenhausen, Franz und Johannes ; Catel, Franz Ludwig ; Reinhart, Johann Christian ; Schnorr von Carolsfeld, Julius ; Ritter von Führich, Joseph ; Dahl, Johan Christian ; Grimm, Ludwig Emil ; etc.
boek